The modification of the wetting of polycaprolactone nanofibre layers via alternating current spinning - Radek Jirkovec; Tomas Kalous; Jiri Chvojka (Materials & Design, 2021)
The study addresses the modification of the wetting of fibrous layers of polycaprolactone via alternating current spinning. The production of the fibre layers considered in the study was initiated using a function generator. The shifting of the offset to the limits of the transmitted amplitude resulted in the production of wettable fibrous layers with high surface energy values. The study revealed that the frequency of alternating spinning affects the surface energy value. Thus, by changing the alternating spinning frequency, it is possible to change the wettability of the produced fibre layers. The study concluded that it is possible to predict the contact angle via the application of the Kwok-Neumann model, as well as the use of the surface tension values of the gelatin hydrogel and the surface energies of the fibre layers produced.